Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper explores policies to drive diversification for Saudi Arabia. Diversification is needed to create jobs for Saudis and to mitigate the impact of uncertainty in oil markets. Although the business climate should be improved, and remaining infrastructure gaps addressed, reforms need to go beyond these areas. Diversification in Saudi Arabia that creates jobs for nationals could be held back by the effects of relatively high wages and their impact on cost competitiveness. Creative solutions are needed to address the impact of high government wages and employment on competitiveness. Industrial policy could help overcome the incentives that encourage companies to focus on the nontradable sector, but should be handled carefully, keeping lessons from other countries' experiences in mind. Export orientation and competition are crucial mechanisms to ensure discipline. Strengthening human capital to raise productivity and provide workers with the skills needed in the private sector will be essential to success.